Strategy of intentional limited resection for lung adenocarcinoma in situ - Koike, Terumoto; Koike, Teruaki; Nakamura, Masaya; Shimizu, Yuki; Goto, Tatsuya; Sato, Seijiro; Tsuchida, Masanori (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
The current issue of European Journal of Cardio-Thoracic Surgery published the remarkable work of Sagawa and associates (1), which demonstrated excellent postoperative outcomes following limited resection for small-sized lung ground-glass opacity (GGO) with an intraoperative pathological diagnosis of bronchioloalveolar carcinoma (BAC).